Outflankers or Outflanked? Investigating the Concept of Organizational Outflanking Through Power, Its Forms and Practice - Alraies, Fadiah (The Arab Journal of Administration, 2024)
Organizational outflanking refers to the possession of organizational resources, which used to provide an advantage for some over others, leading to benefits or gains for the outflankers in comparison to the implicit violation of the rights of the outflanked. Whilst organizational outflanking has important consequences for organizations, affecting productivity, satisfaction and performance of employees, little attention is paid to this important phenomenon in management and organization literature. The current paper, therefore, aimed to consolidate existing knowledge and promote the importance of the concept with regard to organizational behaviour. Given the limited knowledge on the topic, a scoping review of the literature conducted, in order to explore all available material on the concept of organizational outflanking and its use within previous research. Existing literature has touched on the concept of organizational outflanking in several important ways: examining its relationship with power; highlighting its operation on different levels and exploring how it is practised within organizations. There is some ambiguity, however, surrounding the potential identities of the outflanked and the outflankers. Furthermore, little attention paid to the causal factors of outflanking, beyond power relations. Whilst outflanking has shown that predominantly lead to negative outcomes, there is evidence of positive consequences within specific contexts, which requires further exploration. This paper thus provides consolidated knowledge on the concept of organizational outflanking, drawing together existing understandings, raising some important questions that not answered yet, which emerge from the literature. Finally, this paper gives some significant practical implications to the leaders who are the most responsible in managing the outflanking in the organizations.